Assessing Survey Satisficing: The Impact of Unmotivated Questionnaire Responding on Data Quality. (December 2021) - Vriesema, Christine Calderon; Gehlbach, Hunter
Education researchers use surveys widely. Yet, critics question respondents' ability to provide high-quality responses. As schools increasingly use student surveys to drive local policy making, respondents' (lack of) motivation to provide quality responses may threaten the wisdom of using questionnaires for data-based decision making. To better understand student satisficing—the practice of suboptimal responding on surveys—and its impact on data quality, we examined its pervasiveness and impact on a large-scale social–emotional learning survey administered to 409, 721 elementary and secondary students. Findings indicated that despite the prevalence of satisficing, its impact on data quality appeared more modest than anticipated. We conclude by outlining an accessible approach for defining and calculating satisficing for researchers, practitioners, and policymakers.